Differential Axonal Projection of Mitral and Tufted Cells in the Mouse Main Olfactory System - Nagayama, Shin; Enerva, Allicia; Fletcher, Max L.; Masurkar, Arjun V.; Igarashi, Kei M.; Mori, Kensaku; Chen, Wei R. (Frontiers in Neural Circuits, 2010)
In the past decade, much has been elucidated regarding the functional organization of the axonal connection of olfactory sensory neurons to olfactory bulb (OB) glomeruli. However, the manner in which projection neurons of the OB process odorant input and send this information to higher brain centers remains unclear. Here, we report long-range, large-scale tracing of the axonal projection patterns of OB neurons using two-photon microscopy. Tracer injection into a single glomerulus demonstrated widely distributed mitral/tufted cell axonal projections on the lateroventral surface of the mouse brain, including the anterior/posterior piriform cortex (PC) and olfactory tubercle (OT). We noted two distinct groups of labeled axons: PC-orienting axons and OT-orienting axons. Each group occupied distinct parts of the lateral olfactory tract. PC-orienting axons projected axon collaterals to a wide area of the PC but only a few collaterals to the OT. OT-orienting axons densely projected axon collaterals primarily to the anterolateral OT (alOT). Different colored dye injections into the superficial and deep portions of the OB external plexiform layer revealed that the PC-orienting axon populations originated in presumed mitral cells and the OT-orienting axons in presumed tufted cells. These data suggest that although mitral and tufted cells receive similar odor signals from a shared glomerulus, they process the odor information in different ways and send their output to different higher brain centers via the PC and alOT.